Testing oral D-xylose absorption as test intestina.l Normal values ​​in our environment and Literature Review - Ramírez Ramos, Alberto (1962)
A review of the literature on current concepts of absorption, metabolism and excretion of d-xylose and importance of this test as an index of intestinal absorption is made. Values ​​of urinary excretion of d-xylose obtained in our midst, in 10 normal subjects after administration of 25 g is reported. of the substance orally.